1989
DOI: 10.1016/s0022-5347(17)38658-5
|View full text |Cite
|
Sign up to set email alerts
|

Continent Urostomy with Hydraulic Ileal Valve in 136 Patients: 13 Years of Experience

Abstract: The hydraulic ileal valve, which we developed in 1975, ensures continence by adapting to 5 different urinary reservoirs. The valve is made by isolating a 14 cm. long intestinal loop with the mesentery. The isolated ileal segment then is folded inward on itself throughout its entire length. We performed 136 continent urostomies with this hydraulic valve. An ileocecal reservoir was used in 122 patients, ileum in 8, sigmoid in 1, rectum in 1 and bladder (continent cystostomy) in 4. Indications for continent urost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 6 publications
1
16
0
2
Order By: Relevance
“…Despite the social and psychologi cal disadvantages of urinary drainage into an external reservoir, this method remains standard today. Prompted by the work of Kock and Skinner et al [4,5], great interest is now being shown in bladder replacement with detubularized sections of intestine [4][5][6][7][8][9][10]. The creation of a lowpressure reservoir with sufficient capacity and an antirefluxive implantation of the ureters into the pouch assures continence over longer periods, without putting the upper urinary tract at risk.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the social and psychologi cal disadvantages of urinary drainage into an external reservoir, this method remains standard today. Prompted by the work of Kock and Skinner et al [4,5], great interest is now being shown in bladder replacement with detubularized sections of intestine [4][5][6][7][8][9][10]. The creation of a lowpressure reservoir with sufficient capacity and an antirefluxive implantation of the ureters into the pouch assures continence over longer periods, without putting the upper urinary tract at risk.…”
Section: Introductionmentioning
confidence: 99%
“…Close inspection, however, reveals that such favorable ultimate outcomes are often achieved in a setting where intercurrent complications arise in the continent urinary diversion. Close surveillance, mandatory in management of the continent urinary reservoir, can lead to early recognition of such adverse developments and the surgical correction thereof.The present authors and other investigators have previously reported on the early outcomes of the urinary-pressure valve efferent continent reservoir limb, based on the initial work of Benchekroun et al [1,6,11,16]. Early results indicated a potential advantage for this approach as compared with other forms of continent diversion [6,11].…”
mentioning
confidence: 80%
“…The present authors and other investigators have previously reported on the early outcomes of the urinary-pressure valve efferent continent reservoir limb, based on the initial work of Benchekroun et al [1,6,11,16]. Early results indicated a potential advantage for this approach as compared with other forms of continent diversion [6,11].…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…How ever, the intended continence of the valve cannot be achieved in some patients [7][8][9][10][11], Besides, the ileum may be unavailable to construct a valve when the patient has a history of irradiation over the lower abdomen. The con struction of a continent valve using a gastric segment is considered to be an alternative for such patients.…”
Section: Introductionmentioning
confidence: 99%